Rejoinder to Barnett and Block on the Ethics of Loan Maturity Mismatching - Davidson, Laura (MISES: Interdisciplinary Journal of Philosophy, Law and Economics, 2016)
Davidson (2015) takes the position that it is ethical for a bank to borrow money for a shorter time period, and lend this same money out for a longer term. Barnett and Block (forthcoming) disagree. The present paper is a response to Barnett and Block.